ANALISIS PERAN PEKERJA SOSIAL DALAM PENANGANAN ANAK KORBAN KEKERASAN SEKSUAL PADA DINAS SOSIAL KABUPATEN TORAJA UTARA - Banne Rerung Allo; Baharuddin; Agustinus Ba’ka (Paulus Journal of Accounting (PJA), 2024)
This study analyzes the role of social workers (Peksos) in handling child victims of sexual violence in North Toraja Regency. Using a qualitative approach, this study explores the main tasks of Peksos, such as initial assessment, psychosocial intervention, legal assistance, social reintegration, and advocacy. The results of the study indicate that the role of Peksos is very important in supporting victim recovery, but its effectiveness is hampered by minimal resources, social stigma, and weak cross-agency coordination. This study provides strategic recommendations, including trauma-based training, increased collaboration between agencies, and community education. These findings are expected to strengthen the child protection system in North Toraja and become a model for other areas with similar contexts.